SARS-CoV-2 Antibody Avidity Responses in COVID-19 Patients and Convalescent Plasma Donors - Benner, Sarah E; Patel, Eshan U; Laeyendecker, Oliver; Pekosz, Andrew; Littlefield, Kirsten; Eby, Yolanda; Fernandez, Reinaldo E; Miller, Jernelle; Kirby, Charles S; Keruly, Morgan; Klock, Ethan; Baker, Owen R; et al. (The Journal of infectious diseases, 2020)
Abstract Background Convalescent plasma therapy is a leading treatment for conferring temporary immunity to COVID-19–susceptible individuals or for use as post-exposure prophylaxis. However, not all recovered patients develop adequate antibody titers for donation and the relationship between avidity and neutralizing titers is currently not well understood. Methods SARS-CoV-2 anti-spike and anti-nucleocapsid IgG titers and avidity were measured in a longitudinal cohort of COVID-19 hospitalized patients (n = 16 individuals) and a cross-sectional sample of convalescent plasma donors (n = 130). Epidemiologic correlates of avidity were examined in donors by linear regression. The association of avidity and a high neutralizing titer (NT) were also assessed in donors using modified Poisson regression. Results Antibody avidity increased over duration of infection and remained elevated. In convalescent plasma donors, higher levels of anti-spike avidity were associated with older age, male sex, and hospitalization. Higher NTs had a stronger positive correlation with anti-spike IgG avidity (Spearman ρ = 0.386; P < .001) than with anti-nucleocapsid IgG avidity (Spearman ρ = 0.211; P = .026). Increasing levels of anti-spike IgG avidity were associated with high NT (≥160) (adjusted prevalence ratio = 1.58 [95% confidence interval = 1.19–2.12]), independent of age, sex, and hospitalization. Conclusions SARS-CoV-2 antibody avidity correlated with duration of infection and higher neutralizing titers, suggesting a potential alternative screening parameter for identifying optimal convalescent plasma donors. Evaluation of antibody avidity from potential convalescent plasma donors and hospitalized COVID-19 patients suggests increased SARS-CoV-2 IgG avidity is associated with being older, male, and hospitalized. Avidity is correlated with neutralizing titers offering a potential screening parameter for convalescent donors.